Recent Trends in Applied Artificial Intelligence 26th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems, IEA/AIE 2013, Amsterdam, The Netherlands, June 17-21, 2013, Proceedings - Ali, Moonis; Bosse, Tibor; Hindriks, Koen V.; Hoogendoorn, Mark.; Jonker, Catholijn M.; Treur, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume constitutes the thoroughly refereed conference proceedings of the 26th International Conference on Industrial Engineering and Other Applications of Applied Intelligence Systems, IEA/AIE 2013, held in Amsterdam, The Netherlands, in June 2013. The total of 71 papers selected for the proceedings were carefully reviewed and selected from 185 submissions. The papers focus on the following topics: auctions and negotiation, cognitive modeling, crowd behavior modeling, distributed systems and networks, evolutionary algorithms, knowledge representation and reasoning, pattern recognition, planning, problem solving, robotics, text mining, advances in recommender systems, business process intelligence, decision support for safety-related systems, innovations in intelligent computation and applications, intelligent image and signal processing, and machine learning methods applied to manufacturing processes and production systems.
Auctions and Negotiation -- Developing Online Double Auction Mechanism for Fishery Markets -- A Mediator-Based Agent Negotiation Protocol for Utilities That Change with Time -- Cognitive Modeling -- Learning Parameters for a Cognitive Model on Situation Awareness -- Fostering Social Interaction of Home-Bound Elderly People: The EasyReach System -- Cooperative Games with Incomplete Information among Secondary Base Stations in Cognitive Radio Networks -- Crowd Behavior Modeling -- Ant Colony Optimisation for Planning Safe Escape Routes -- A Spatio-Temporal Probabilistic Model of Hazard and Crowd Dynamics in Disasters for Evacuation Planning -- Predicting Human Behavior in Crowds: Cognitive Modeling versus Neural Networks -- Distributed Systems and Networks -- Analyzing Grid Log Data with Affinity Propagation -- Using Ising Model to Study Distributed Systems Processing Capability -- Evolutionary Algorithms -- Computing the Consensus Permutation in Mallows Distribution by Using Genetic Algorithms -- A Hybrid Genetic Algorithm for the Maximum Satisfiability Problem -- Knowledge Representation and Reasoning -- An Object Representation Model Based on the Mechanism of Visual Perception -- Web Metadata Extraction and Semantic Indexing for Learning Objects Extraction -- Pattern Recognition -- Approximately Recurring Motif Discovery Using Shift Density Estimation -- An Online Anomalous Time Series Detection Algorithm for Univariate Data Streams.-Assisting Web Site Navigation through Web Usage Patterns -- Planning -- GRASPing Examination Board Assignments for University-Entrance Exams -- A Greedy Look-Ahead Heuristic for the Container Relocation Problem -- Integrating Planning and Scheduling in the ISS Fluid Science Laboratory Domain -- Efficient Identification of Energy-Optimal Switching and Operating Sequences for Modular Factory Automation Systems -- Problem Solving -- The Two-Dimensional Vector Packing Problem with Courier Cost Structure -- Penguins Search Optimization Algorithm (PeSOA) -- A Bidirectional Building Approach for the 2D Guillotine Knapsack-Packing Problem -- Increasing the Antibandwidth of Sparse Matrices by a Genetic Algorithm.-A New GA-Based Method for Temporal Constraint Problems -- On Using the Theory of Regular Functions to Prove the Optimality of the Continuous Pursuit Learning Automaton -- Robotics -- Online Exploratory Behavior Acquisition of Mobile Robot Based on Reinforcement Learning -- Improved Sound Source Localization and Front-Back Disambiguation for Humanoid Robots with Two Ears -- Designing and Optimization of Omni-Directional Kick for Bipedal Robots -- Aerial Service Vehicles for Industrial Inspection: Task Decomposition and Plan Execution.-A BSO-Based Algorithm for Multi-robot and Multi-target Search -- Text Mining -- Economic Sentiment: Text-Based Prediction of Stock Price Movements with Machine Learning and WordNet -- Feature Extraction Using Single Variable Classifiers for Binary Text Classification -- An Approach to Automated Learning of Conceptual Graphs from Text -- Semi-supervised Latent Dirichlet Allocation for Multi-label Text Classification -- Special Session on Advances in Recommender Systems -- Recommending Interest Groups to Social Media Users by Incorporating Heterogeneous Resources -- Recent Advances in Recommendation Systems for Software Engineering -- WE-DECIDE: A Decision Support Environment for Groups of Users -- Special Session on Business Process Intelligence Logic-Based Incremental Process Mining in Smart Environments -- Information Mining Processes Based on Intelligent Systems -- Customer Churn Detection System: Identifying Customers Who Wish to Leave a Merchant -- Special Session on Decision Support for Safety related Systems Hazard Identification of the Offshore Three-Phase Separation Process Based on Multilevel Flow Modeling and HAZOP -- Multilevel Flow Modeling Based Decision Support System and Its Task Organization -- Simulation-Based Fault Propagation Analysis – Application on Hydrogen Production Plant -- Automatic Decomposition and Allocation of Safety Integrity Levels Using a Penalty-Based Genetic Algorithm -- HAZOP Analysis System Compliant with Equipment Models Based on SDG -- Special Session on Innovations in Intelligent Computation and Applications -- TAIEX Forecasting Based on Fuzzy Time Series and Technical Indices Analysis of the Stock Market -- Hierarchical Gradient Diffusion Algorithm for Wireless Sensor Networks -- Constructing a Diet Recommendation System Based on Fuzzy Rules and Knapsack Method -- An Intelligent Stock-Selecting System Based on Decision Tree Combining Rough Sets Theory -- Cloud-Based LED Light Management System and Implementation Based-on Wireless Communication -- A Study on Online Game Cheating and the Effective Defense -- Credit Rating Analysis with Support Vector Machines and Artificial Bee Colony Algorithm -- An ACO Algorithm for the 3D Bin Packing Problem in the Steel Industry -- Special Session on Intelligent Image and Signal Processing Controlling Search Using an S Decreasing Constriction Factor for Solving Multi-mode Scheduling Problems -- Extracting Blood Vessel in Sclera-Conjunctiva Image Based on Fuzzy C-means and Modified Cone Responses -- A Spherical Coordinate Based Fragile Watermarking Scheme for 3D Models - Palm Image Recognition Using Image Processing Techniques -- Liver Cell Nucleuses and Vacuoles Segmentation by Using Genetic Algorithms for the Tissue Images -- Mouth Location Based on Face Mask and Projection -- Environmental Background Sounds Classification Based on Properties of Feature Contours -- On the Prediction of Floor Identification Credibility in RSS-Based Positioning Techniques -- A Study of Vessel Origin Detection on Retinal Images -- The Tires Worn Monitoring Prototype System Using Image Clustering Technology -- Quality Assessment Model for Critical Manufacturing Process of Crystal Oscillator -- Local Skew Estimation in Moving Business Cards -- Special Session on Machine Learning Methods -- Applied to Manufacturing Processes and Production Systems Imbalanced Learning Ensembles for Defect Detection in X-Ray Images -- Improvements in Modelling of Complex Manufacturing Processes Using Classification Techniques -- A Study on the Use of Machine Learning Methods for Incidence Prediction in High-Speed Train Tracks -- Estimating the Maximum Shear Modulus with Neural Networks.
Keywords: Artificial intelligence; Application software; Algorithms; Data mining; Optical data processing; Computer science; Artificial Intelligence; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Science, general